Invasive Radiation Diagnostic Methods - Jo‘rayevna, Odilova Nilufar; qizi, Odilova Ezoza Ulug‘bek; Baxtiyorovna, Elmurotova Dilnoza (American Journal of Bioscience and Clinical Integrity, 2025)
This paper examines invasive radiation diagnostic methods. It is shown that angiography is one of the most modern radiological methods for assessing vascular patency, while coronary angiography evaluates the condition of the heart vessels. Radioisotope diagnostics, or scintigraphy, based on the use of radioactive isotopes to detect the absence or presence of various diseases.